1996
DOI: 10.1007/bf00035275
|View full text |Cite
|
Sign up to set email alerts
|

Measuring field resistance of cabbage cultivars to black rot

Abstract: Disease progress and gradient curves of black rot on cabbage were evaluated in field plots of the cultivars Bartolo, Erdeno, Perfect Ball, and Roxy in The Netherlands during 1991 and. Plots were inoculated by single sources in the centre of each plot. Individual plants were examined for disease incidence and severity. Disease progress was described by the Gompertz model. The overall measure of absolute rate (disease progress rate r multiplied with maximum disease intensity K) was used to compare cultivar effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…Kocks and Ruissen (1996) showed that increased field resistance reduced the development of black rot in time and space in cabbage. Resistance to Xcc has been identified in different genotypes of B. oleracea (Bain, 1952;Williams et al, 1972;Hunter et al, 1987;Henz and Melo, 1994;Sharma et al, 1995;Taylor et al, 2002;Griesbach et al, 2003), including commercially available cultivars of cabbage , Griesbach et al, 2003, and a series of inbreds, Badger I-14 to I-20, released for breeding programmes Williams, 1980) with resistance introduced from cv.…”
Section: Introductionmentioning
confidence: 98%
“…Kocks and Ruissen (1996) showed that increased field resistance reduced the development of black rot in time and space in cabbage. Resistance to Xcc has been identified in different genotypes of B. oleracea (Bain, 1952;Williams et al, 1972;Hunter et al, 1987;Henz and Melo, 1994;Sharma et al, 1995;Taylor et al, 2002;Griesbach et al, 2003), including commercially available cultivars of cabbage , Griesbach et al, 2003, and a series of inbreds, Badger I-14 to I-20, released for breeding programmes Williams, 1980) with resistance introduced from cv.…”
Section: Introductionmentioning
confidence: 98%
“…In the present study, a single source of infection was not able to infect (resulting in symptom expression) a single plot completely. Such a limited infection potential was also found with cabbage refuse piles (Kocks & Zadoks, 1996) and with single source inoculations to test field resistance of cabbage against black rot (Kocks & Ruissen, 1996). Nevertheless, farmers are confronted with completely infected cabbage fields.…”
Section: Spatio-temporal Developmentmentioning
confidence: 77%
“…Although Kocks & Ruissen (1996) suggested the Gompertz model to analyse temporal progress of black rot, a log-logistic model was chosen here. The results indicated that spatio-temporal development and initial inoculum are related.…”
Section: Spatio-temporal Developmentmentioning
confidence: 99%
“…A dificuldade na obtenção de estimativas precisas das taxas de progresso da severidade das doenças, como verificado na maioria das situações utilizando os dados originais ou transformados para os modelos exponencial, monomolecular, logístico e de Gompertz, pode estar associada aos baixos valores das proporções de severidade, muitos deles inferiores a 0,05, como verificado em outros patossistemas (Plaut & Berger, 1981). Apesar do modelo de Gompertz ter sido apropriado para estimar taxas epidêmicas com valores muito baixos de severidade da alternariose em repolho na Flórida (Fontem et al, 1991), bem como para a podridão negra, cujos os sítios de infecção tornam-se menos suscetíveis com a idade (Kocks & Ruissen, 1996), no presente estudo essas características do modelo de Gompertz não ficaram evidentes na maioria das vezes.…”
Section: Discussionunclassified
“…Para efeito de comparação, considerando o modelo de Gompertz, as taxas de progresso da severidade da podridão negra no Agreste de Pernambuco (0,002 ≤ k ≤ 0,029) foram menores que as verificadas por Kocks & Ruissen (1996) ao analisarem o progresso dessa doença na Holanda (0,03 ≤ k ≤ 0,14). Em relação à alternariose, considerando o modelo logístico, as taxas de progresso da severidade em Pernambuco (0,023 ≤ k ≤ 0,075) também foram menores que as obtidas por Fontem et al (1991) na Flórida (0,06 ≤ k ≤ 0,11).…”
Section: Discussionunclassified